Relationship between Microscopic Agglutination Test and Real-Time PCR Assay for Detection of Seropositivity of Pathogenic Leptospira Infections in Cattle in Chile: A Pilot Study - Paz Loebel; Lucía Azócar-Aedo; Alfredo Rodríguez; María Gallardo (Zoonoses)
<!-- named anchor --> Objectives: This study was aimed at evaluating the relationship between microscopic agglutination test (MAT) seropositivity and real-time polymerase chain reaction (PCR) reactivity in cattle. An additional objective was assessment of the diagnostic value of both tests in detecting seropositivity and infection caused by pathogenic Leptospira. <!-- named anchor --> Methods: Blood and urine samples were collected from 61 bovines in the Los Lagos region of Chile. The MAT detected a panel of eight Leptospira serogroups, whereas real-time PCR was conducted with a TaqMan probe targeting the